A photo-induced colorimetric reaction of N, N'-bis[2-(trimethylammonium)ethyl]-1, 8:4, 5-naphthalenetetracarboxdiimide for detection of carboxylate anions. (22nd June 2022) - Izawa, Hironori; Yasufuku, Fumika; Matsumoto, Tomoko; Ifuku, Shinsuke; Saimoto, Hiroyuki; Sumita, Masato
Graphical abstract: Abstract: Here we show a novel colorimetric sensor system with a photo-induced colorimetric reaction of N, N' -bis[2-(trimethylammonium)ethyl]-1, 8:4, 5-naphthalenetetracarboxdiimide (TENDI) to detect and quantify carboxylate derivatives. In the presence of CH3 COONa, TENDI aqueous solution under UV irradiation shows a photo-induced colorimetric reaction, which is due to the production of naphthalenediimide (NDI)-based radical anions whose absorbance peaks appear at around 400–600 nm. In contrast, no color changes are observed in the cases of diverse inorganic salts. In addition, TENDI shows another ability to discriminate the structural features of carboxylate derivatives by color tone. Moreover, interestingly, the Hill equation can approximate the relationship between carboxylate concentrations and absorbance values on the maximum absorbance wavelengths of the absorbance peaks due to the NDI-radical anions.